Trends in Leadership at Spine Surgery Fellowships. Issue 10 (15th May 2020) - Donnally, Chester J.; Schiller, Nicholas C.; Butler, Alexander J.; Sama, Andrew J.; Bondar, Kevin J.; Goz, Vadim; Shenoy, Kartik; Vaccaro, Alexander R.; Hilibrand, Alan S.
Abstract : Study Design: Cross-sectional study. Objective: To illustrate demographic trends among spine fellowship leaders (FLs). Summary of Background Data: No previous study in the orthopedic literature has analyzed the demographic characteristics or past surgical training of FL in an orthopedic sub-specialty. We attempt to illustrate demographic trends among spine fellowship leadership including fellowship directors (FDs) and co-fellowship directors (co-FDs). We also highlight the institutions that have trained these leaders at various levels. Methods: Our search for FDs was constructed from the 2018 to 2019 North American Spine Surgery (NASS) Fellowship Directory. Datapoints gathered included: age, sex, residency/fellowship training location, time since training completion until FD appointment, length in FD role, and personal research H-index. Results: We identified 103 FLs consisting of 67 FDs, 19 co-FDs, and another 16 individuals with a synonymous leadership title. 96.1% (99) of the leadership consisted of males while 3.9% (4) were female. The mean age was 52.9 years old and the mean h-index of the FLs was 23.8. FLs were trained in orthopedic surgery (n = 89), neurosurgery (n = 13), or combined orthopedic surgery and neurosurgery training (n = 1). The top fellowships programs producing future FLs were: Case Western Reserve University, Cleveland (n = 10), Washington University, St. Louis (n = 9), and Rothman Orthopaedic Institute, Thomas Jefferson University, Philadelphia (n = 7). Conclusion: Spine surgery fellowship directors are more likely to have graduated from certain residency and fellowship programs. This finding could be a result of the training provided by these centers or the institution's predilection to select applicants that are more likely to later seek academic leadership roles post-training. Level of Evidence: 4 Abstract : Spine fellowship leaders are more likely to have trained at from certain institutions. This finding may be attributed to the training provided or the institutions' predilections to select applicants that are more likely to seek academic leadership roles.